Between Dogma and Lifestyle: Reinterpreting the Hijab in the Era of Commodification through the Perspectives of Mernissi and Wadud - Bayu Firman Alamsyah; Mundhir (Jurnal test, 2026)
This study is motivated by the theological and sociological tensions in contemporary hijab phenomena, where symbols of piety are often reduced by the commodification of the fashion industry. This study aims to deconstruct the static understanding of hijab and reformulate the concept of decency amidst the currents of lifestyle trends. Employing a qualitative library research method with a comparative approach, this research synthesizes the critical thought of Fatima Mernissi (historical deconstruction) and the tawhidic hermeneutics of Amina Wadud (substance reconstruction). The results indicate that the hijab is not an ahistorical dogma, but a dynamic cultural medium. The main finding of this study is the concept of “contextual ethics of decency” as a middle path; a synthesis positing that clothing forms may change according to the context of the times (per Mernissi’s historical critique), provided that the principles of moral integrity and piety remain its core essence (per Wadud’s interpretation). This study concludes that the desacralization of hijab by the market need not be responded to with anti-modernity rejection, but rather with the strengthening of women’s moral agency. Consequently, the parameters of piety shift from visual formalism to dignified public ethics, providing theoretical legitimacy for modest fashion as a valid yet spiritual expression of identity.